2012
DOI: 10.1007/s13337-012-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Phylogenetically Distinct Isolates of Grapevine fanleaf virus from Iran Based on 2AHP Gene

Abstract: Movement and coat protein genes from Grapevine fanleaf virus (GFLV) isolates have been characterized previously from Iran. In this study, an optimized reverse transcription polymerase chain reaction protocol was established to amplify RNA2 genomic segment corresponding to the hypothetical protein (2A HP ). The sequence of 2A HP was compared with that of previously reported GFLV strains/isolates from other countries which showed 82-86% sequence identities. The 2A HP gene from Iran appeared to be standing distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Considering the abundance of nepovirus species such as GFLV, GDefV, and ArMV in grapevine libraries, it is likely that decline and stunting symptoms of grapevines in the surveyed vineyards are caused by infectious degeneration syndrome induced by nepoviruses [ 6 ], although mosaic and fanleaf symptoms are not observed on grapevine leaves. Previous reports also indicate that Iranian GFLV isolates represent a divergent group in the GFLV population [ 24 , 68 , 69 ], and Vitis vinifera cultivars in Iran do not show severe and clear symptoms of GFLV infection [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the abundance of nepovirus species such as GFLV, GDefV, and ArMV in grapevine libraries, it is likely that decline and stunting symptoms of grapevines in the surveyed vineyards are caused by infectious degeneration syndrome induced by nepoviruses [ 6 ], although mosaic and fanleaf symptoms are not observed on grapevine leaves. Previous reports also indicate that Iranian GFLV isolates represent a divergent group in the GFLV population [ 24 , 68 , 69 ], and Vitis vinifera cultivars in Iran do not show severe and clear symptoms of GFLV infection [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the satRNA sequences from Iran with the previously reported satRNA sequences suggested that the former were phylogenetically close to that reported from Slovenia and Central Europe, however, the reported satRNA sequences in this study are placed in a distinct sub clade on the phylogenetic tree. The previous studies on CP and MP genes of GFLV in Iran have shown the distinctness of Iran isolates among all the reported GFLV sequences from around the world (Sokhandan et al 2012). So, the distinct positions of satRNAs from Iran in the phylogenetic tree could be because of the distinctness of the helper virus.…”
Section: Glasshouse Studiesmentioning
confidence: 93%
“…The genetic variation in the flanking sequences of satRNA and failure in the primer annealing process might be the reason for unsuccessful RT-PCR amplification once other primers were used. Also, previous studies on Iran isolates of GFLV have revealed that they possess distinct genotypes, consequently the primers which were designed based on exotic GFLV isolates could not be efficient in annealing the local isolates (Sokhandan et al 2012). Among the newly designed primers, Gf750/Gr750 had a better amplification thus were utilized in the study.…”
Section: Glasshouse Studiesmentioning
confidence: 99%
“…It is estimated that the global loss of over 1 billion US dollars is due to viral infection in only vineyards (Mckenzie and Pathirana, 2007). Despite the conducted studies relating to grapevine, the necessity to identify and control viruses is still main issue (Bashir et al, 2009;Sokhandan-Bashir et al, 2012). The first step to control the viral diseases is to identify the virus.…”
Section: Introductionmentioning
confidence: 99%